2021
DOI: 10.1021/acsami.1c09933
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape Control of Ice Crystals by Amphiphilic Block Copolymers and Their Implication in the Cryoprotection of Mesenchymal Stem Cells

Abstract: Precise control over the size and shape of ice crystals is a key factor to consider in designing antifreezing and cryoprotecting molecules for cryopreservation of cells. Here, we report that a poly(ethylene glycol)−poly(L-alanine) (PEG−PA) block copolymer exhibits excellent cryoprotecting properties for stem cells and antifreezing properties for water. As the molecular weight of PA increased from 500, 760, and 1750 Da (P1, P2, and P3) at the same PEG molecular weight of 5000 Da, the β-sheet content decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 64 publications
0
45
0
Order By: Relevance
“…Ice crystals which are sharp and long may be advantageous to cryoablation if the intracellular ice crystals can pierce into organelles or the cell membrane. For instance, it was recently reported that aqueous dispersions of poly(ethylene glycol)-poly(l-alanine) (PEG-PA) could form round ice crystals while poly(vinyl alcohol) (PVA) could form needle-like crystals 197 . PEG-PA had high cryoprotection while PVA did not.…”
Section: Nanomaterials In Cryoablation: a New Opportunitymentioning
confidence: 99%
“…Ice crystals which are sharp and long may be advantageous to cryoablation if the intracellular ice crystals can pierce into organelles or the cell membrane. For instance, it was recently reported that aqueous dispersions of poly(ethylene glycol)-poly(l-alanine) (PEG-PA) could form round ice crystals while poly(vinyl alcohol) (PVA) could form needle-like crystals 197 . PEG-PA had high cryoprotection while PVA did not.…”
Section: Nanomaterials In Cryoablation: a New Opportunitymentioning
confidence: 99%
“…Cell recovery was assayed using trypan blue staining after cell plating in a 24-well culture plate. , All live and dead cells were resuspended in DMEM growth media (1 mL). The same number of live cells (5 × 10 4 live cells/well) was added to a 24-well culture plate.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…In particular, DMSO used in the traditional cryopreservation system is toxic, and it damages mitochondria, interferes with intracellular cell signaling, and affects the differentiation of stem cells. Therefore, a very strict procedure for the postremoval of DMSO is required for in vivo as well as in vitro applications. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, self-assembling polymers have been reported as IRI-active compounds. The control of hydrophobic and hydrophilic balance is a key factor again in the design of these polymers because they need to adhere to the ice crystal surface rather than self-assembling. , Vitrification is another method to avoid ice crystallization, where a high concentration of cryoprotectants and a fast cooling procedure inhibit ice crystal formation. , …”
Section: Introductionmentioning
confidence: 99%